REFUGEES RESETTLEMENT: A REVIEW OF INDONESIAN LAWS AND PRACTICES - Afriansyah, Arie; Zulfa, Eva Achjani (Indonesia Law Review, 2018)
This research analyzes the legal aspects of resettlement within the context of Indonesian law. First, it discusses the laws that related to the interaction between refugees and the Indonesian people. Second, this research will discuss how Indonesia applies Indonesian national law when it comes to the treatment of refugees during their period of resettlement. Third, this research will offer a proposal in regards to the structuring of national policy in terms of how the treatment of asylum seekers that have received refugee status as they await the process of resettlement. In cohesion to these three notions, this research utilizes a judicial-normative approach to analyze the doctrines as well as the requirements in international law as well as the concept and the opinions of scholars combine with rules found within national laws about the procedure of resettlement of a third party state for the refugees. By observing refugee camps in Jakarta, Medan and Kupang during 2016, it concludes that national immigration law in Indonesia is heavily embedded within the Law No. 6/2011 about immigration and the Director-General’s decision No. IMI-1489.UM.08.06 at the year 2010 about the handling of illegal immigrants. Further, this article argues on the need of regulatory measures in place in regards to the capacity of institutions in Indonesia in the handling of refugees so that more extensive coordination can be achieved in.